Vital dye immersion evaluations with juvenile delta smelt. Issue 1 (26th December 2022) - Afentoulis, Virginia; Kalmbach, Andrew; Hung, Tien‐Chieh; Rahman, Md. Moshiur; Ellison, Luke; Miranda, Javier
Abstract: Immersion‐based vital dyes were tested as a marking method for use in larval smelt mark–recapture studies. We assessed five fluorescent dyes as a mark for juvenile osmerids: 4‐Di‐1‐ASP, BODIPY FL C12, BODIPY 505/515, Nile red, and calcein. We marked juvenile Delta Smelt, Hypomesus transpacificus, as a proxy for Longfin Smelt, Spirinchus thaleichthys, to determine the efficacy of each as a batch marking technique for osmerids based on dye performance and survival. All groups of Delta Smelt including control groups exhibited high mortality (71%–100%, 5 days after trial), and lowest survival was observed in 4‐Di‐1‐ASP‐treated fish. Highest survival was observed in Nile red‐ and BODIPY FL C12‐treated fish. Fluorescence observations indicated that the brightest, visible fluorescence was seen in calcein and to a lesser extent, 4‐Di‐1‐ASP, followed by BODIPY FL C12 and Nile red. In addition to dye performance, it is recommended that immersion techniques that improve survival be considered. Abstract : We assessed five fluorescent dyes as marks for live, juvenile osmerids: 4‐Di‐1‐ASP, BODIPY FL C12, BODIPY 505/515, Nile red, and calcein. All groups of smelt including control groups exhibited high mortality, and lowest survival was observed in 4‐Di‐1‐ASP‐treated fish. Fluorescence observations indicated that the brightest, visible fluorescence was seen in calcein and to a lesser extent, 4‐Di‐1‐ASP, followed by BODIPY FL C12 and Nile red.